2022
DOI: 10.26794/2587-5671-2022-26-6-192-211
|View full text |Cite
|
Sign up to set email alerts
|

Financial Technology Adoption – A Case of Indian MSMEs

Abstract: Micro, small, and medium enterprises (MSME) are the backbone of every economy. Financial inclusion of MSMEs is essential for any country aspiring to economic development. Innovative solutions offered by fintech companies can support the financial inclusion of MSMEs. Digital payments, alternative loans, insurance, investments, regulatory, and robo-advisory services are just a few of the services that fintech companies provide to MSMEs. The purpose of this studyis to examine the role of financial technology on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
7
0
2
Order By: Relevance
“…Fintech companies offer innovative solutions that can significantly contribute to the financial inclusion of MSMEs. The findings indicate a high level of financial technology acceptance among the MSME sector, with a majority considering themselves moderate fintech adopters (Gupta, Agarwal & Nautiyal, 2022). MSMEs demonstrate a strong understanding of various financial services offered by fintech companies.…”
Section: Review Of Literaturementioning
confidence: 86%
“…Fintech companies offer innovative solutions that can significantly contribute to the financial inclusion of MSMEs. The findings indicate a high level of financial technology acceptance among the MSME sector, with a majority considering themselves moderate fintech adopters (Gupta, Agarwal & Nautiyal, 2022). MSMEs demonstrate a strong understanding of various financial services offered by fintech companies.…”
Section: Review Of Literaturementioning
confidence: 86%
“…Studies have shown that fintech has the potential to provide access to financial services for underserved populations, including MSMEs, aiding them in breaking free from poverty (Lagna & Ravishankar, 2021;Sudarmo, 2021). MSMEs are increasingly adopting fintech products and services, presenting a growing opportunity for fintech companies, traditional financial institutions, and non-financial organizations to support financial management in this sector (Gupta et al, 2022). Moreover, Sharia fintech has been identified as instrumental in advancing financial inclusion for MSMEs in industries like halal products, where traditional banking services may not be readily accessible (Dewi & Adinugraha, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial Inclusion provides access and opportunities for all individuals, regardless of their economic background, to be involved in creative economic activities (Nainggolan, 2023). Financial inclusion enables individuals or groups who have limited access to traditional sources of funding to gain access to the financing needed to start or grow their creative business (Gupta et al, 2022). Through inclusive financial services such as microcredit, peer-to-peer lending, or crowdfunding models, creative industry players who were previously neglected by traditional financial institutions can access the funds needed to support their creative projects (Yudaruddin, 2023).…”
Section: Journal Of Internationalmentioning
confidence: 99%